Protecting Possession, a Question of Values? A Comparative Inquiry into the Moralization of Possession in Brazil and Canada - Debruche, Anne-Françoise; Tepedino, Gustavo; Renteria, Pablo (Revue générale de droit, 2014)
This paper focuses on possessory protection of immovables (or real property) in Brazilian civil law and Canadian common law. In both jurisdictions, possession enjoys a specific protection or status, which in turn relates to the rest of property law, particularly the law of acquisitive prescription, in a specific way. But in and by itself, despite these conceptual differences, possessory protection in Canada or Brazil works in an objective fashion: it is not denied to possessors in bad faith as a principle. Nonetheless, in both systems, the institutions designed to protect possession have been “moralized” by judges to echo concerns similar to those voiced in relation to acquisitive prescription, but also to emphasize human rights, constitutional values and good faith. In Brazil, this moralization process is the consequence of the emergence of a constitutionalized civil law and of the social function of the right of ownership. In several cases, it has allowed illicit buildings to remain where they are despite the owner’s claim, for instance when a favela has appeared on a land neglected by its owner for years. In England, the possessor’s good faith has been scrutinized through his intent to possess, and under the lenses of the future enjoyment criteria, later rejected by the Court of Appeal. In Canada, the test of the inconsistent use of the land has played the same moralizing role and continues to do so, to deny the benefit of adverse possession to squatters and to prevent them from enjoying possessory protection.